Integrasi Keilmuan dalam Pendidikan Islam Perspektif Pemikiran Ibnu Sina dan Mahmud Yunus - Ulvia Nur Anini; Muh. Ilham R. Kurniawan; Ali Muttaqin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
This article aims to explore the concept of Islamic education thought initiated by Ibnu Sina and Mahmud Yunus. The concept of Islamic education thought both have a relationship with each other. Islamic education according to Ibnu Sina and Mahmud Yunus prioritizes the integration of religious knowledge and general knowledge. The concept of thinking about the goals, methods and curriculum is second and can be used as a philosophical basis in the practice of Islamic education. The balance between the science of religion and the general science that he put forward must be done so that there is no dichotomy of science. Because the purpose of Islamic education is to deliver students to achieve happiness in the world and the hereafter. So that the study of religion and general science is carried out in a balanced manner.